Brief Therapist-Guided Exposure Treatment of Panic Attacks: A Pilot Study. Issue 4 (July 2019) - Hall, Christina Bergmark; Lundh, Lars-Gunnar
A three-session therapist-guided exposure treatment was tested in a consecutive series of eight primary health care patients suffering from panic attacks who specifically used distraction techniques as their primary safety behavior. The Panic Disorder Severity Scale Self-Report (PDSS-SR) was administered at baseline (1-3 weeks before the first session), and 1, 2, and 3 weeks after treatment. Weekly ratings on the Body Sensations Questionnaire (BSQ) and the Agoraphobic Cognitions Questionnaire (ACQ) during treatment were undertaken to explore when reliable change took place on these measures. The results showed a large within-group effect size on PDSS-SR ( d = 1.63); six of the eight patients were classified as responders, and four of them showed remission. Large effect sizes ( d s between 1.17 and 3.00) were seen also on BSQ and ACQ, as well as on agoraphobic avoidance, general level of anxiety, and depression. The results on BSQ and ACQ suggest that the fear of body sensations in most cases was reduced before a change occurred in agoraphobic cognitions. These results indicate that a brief three-session exposure-based treatment may be sufficient for this subgroup of panic patients. The findings need to be replicated under controlled conditions with larger samples and different therapists before more firm conclusions can be drawn. Future research should also focus on the relevance of dividing patients into subgroups based on type of safety behavior.